Apprenticeship and Vocational Education and Training in Israel - Kuczera Małgorzata, Małgorzata (Organization for Economic Cooperation & Development, 2018)
One of a series of studies on vocational education and training, this review assesses the apprenticeship system and vocational education and training in Israel and provides policy recommendations. Israel has experienced strong economic growth over the last decade, and labour shortages are ...